THE GEODESY IN THE HYDOGRAPHY - Krueger, Cláudia Pereira; Souza, Adriano Vieira de (Revista Brasileira de Cartografia, 2014)
The mathematics, the computer science and the physics are the foundations for many sciences, including geodesy. The Geodesy applies those disciplines to determine both size and shape of the Earth using its gravity fi eld. The Hydrography uses geodesy as its main tool to determine, most of the time, the geographical coordinates of nautical features. This paper aims to demonstrate the strong connection between Geodesy and Hydrography, especially from the point of view of the construction of nautical chart.